Feasibility and Effectiveness of a New Short-Term Psychotherapy Concept for Adolescents With Emotional Dysregulation - Dixius, Andrea; Möhler, Eva (Frontiers in Psychiatry, 2021)
Background: START - Stress-Trauma-Symptoms-Regulation-Treatment - is an innovative manualized short-term treatment program for stabilization and stress resilience in emotionally dysregulated adolescents, based on an approach of stress recognition and management and emotional regulation. The manual contains multilingually translated (Dari, Arabic, English, German) therapy materials, numerous pictures, and additionally all info/worksheets as audio files. The current pilot trial aims to assess the feasibility and effectiveness of the START intervention program for improvement of emotion regulation. Methods: In the present study, 66 adolescents between the age of 13 - 18 years admitted to a child psychiatric unit for acute emotional or behavioral dysregulation took part in the START program for 5 weeks in an open group setting with two sessions per week (70 min/session). Before treatment, we determined the current trauma load with the Child and Adolescent Trauma Screen (CATS) and the Child Posttraumatic Cognitions Inventory (CPTCI). Before and after treatment, the participants completed the FEEL-KJ, a self-report screening instrument for emotional regulation. Results: A large proportion of our sample (75%-82%) scored above the cut off for significant trauma as assessed by CATS/CPTCI. The results of the pre-post FEEL-KJ underline that START contributed to a positive effect on emotional regulation. Conclusion: START demonstrates preliminary evidence for improvement in emotional dysregulation after a 5-weeks course of treatment. Therefore, this short-term intervention can possibly be regarded as a tool to improve emotional stability in children with a high load of trauma-related psychopathology. The results are promising and warrant future studies, specifically randomized controlled trials on the effectiveness of START for strengthening resilience in several at-risk-populations.